Are Smoker/Vapers at Risk of Severe COVID-19 Infection? - Risala H. Allami; Ahmed A. Suleiman; Hamid H. Enezei (Al-Anbar Medical Journal)
The recent outbreak of a novel coronavirus has put the world on alert. The World Health Organization (WHO) declared the novel coronavirus disease-2019 (COVID-19) as a pandemic and it has been spreading around the world rapidly [1]. The causative pathogen of a novel coronavirus was subsequently identified and named 2019 novel coronavirus (2019-nCoV). Pneumonia caused by new coronavirus is an acute respiratory infection caused by a coronavirus which is a positive-strand RNA and transmitted from the bat with high homology of a previously identified virus.